Model Pembelajaran Tahfizh Al-Qur’an pada Dayah Ar Raudhah Tahfizh Al-Qur’an Kota Lhokseumawe - Diauddin Diauddin; Abd. Mukti; Yusnaili Budianti (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
This study examines the Tahfizh Al-Qur’an Learning Model. The object of his research is Dayah Ar Raudhah Tahfizh Al-Qur’an Lhokseumawe. Where there is a uniqueness in Dayah Ar Raudhah, namely in the learning model that is carried out which has been proven to have been able to print Al-Qur’an memorization cadres in a shorter time compared to tahfizh Al-Qur’an educational institutions in general. This study aims to analyze the Tahfizh Al-Qur’an learning model at Dayah Ar Raudhah Tahfiz Al-Qur’an Lhokseumawe, Blang mangat District. The type of research used in this research is a qualitative research type. Data collection techniques are carried out through: Observation, interviews and documentation studies. The data analysis technique was carried out by means of data reduction, data presentation, and drawing conclusions. The results showed that, first, the learning model of Dayah Tahfizh Al-Qur’an Ar Raudhah Lhokseumawe used the Ottoman Turkish tahfizh model or known as the backward sequence model with a standard time of memorizing 30 juz for 20. Second, the implementation of the Dayah Tahfizh Al-Qur' learning model. An Ar Raudhah Lhokseumawe was carried out in several stages. The first stage, known as the pre-tahfizh program for 6 months. The second stage, memorizing with the Ottoman model that has been set, is carried out in several steps, (1) Talib reads repeatedly the page to be memorized. (2) Memorizing verse by verse by dividing 1 page into 3 parts, 1 part consisting of 5 lines of verses from the Qur'an, then memorizing 5 lines of verses from the Qur'an from the bottom to the top 5 lines of the beginning of the verse. (3) the memorization of the first round starts from the last page of juz 1 then juz the last page of juz 2, until the last page of juz 30, after that it is continued with the second round starting from the second last page of juz second to the penultimate page of juz the second last page of juz 30 so so on until it's finished. The third stage, the evaluation stage is carried out through 2 stages. The first stage, each talib depositing memorization to his ustadz. The assessment is based on fluency, makaharijul letters and tajwid. Third, constraints in the application of the tahfizh learning model to Dayah Ar Raudhah Tahfizh Al-Qur’an Lhokseumawe. first, feeling difficult when starting to memorize the Qur'an, because memorizing the Qur'an from the last page of each juz. And have to start from the beginning for the talib who had previously memorized the Qur'an. Second, can't confirm or determine how many juz memorized because the system is round.